Techno-Economic Assessment of Dimethyl Ether (DME)Production through Methanol Dehydration Process - Yessa Julyana; Hendriyana; Een Taryana; Handoko Iskandar; Xbal Meiprastyo (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2025)
Dimethyl Ether (DME) is a clean, colorless gas that serves as a potential alternative to liquefied petroleum gas (LPG). This study presents a comprehensive techno-economic assessment of DME production via methanol dehydration with a plant capacity of 20,000 tons per year. The process utilizes an alumina–silicate catalyst in a multitube fixed-bed reactor operating at 300–350°C and 30 bar. Simulation results show a methanol conversion of 85% per pass, achieving a final DME purity exceeding 99.5%. The total capital investment (CAPEX) is estimated at USD 12.8 million, with annual operating costs (OPEX) of approximately USD 13 million. Economic indicators reveal a Net Present Value (NPV) of USD 5.2 million, an Internal Rate of Return (IRR) of 14.5%, a Return on Investment (ROI) between 15–17%, and a payback period of six years. The break-even point (BEP) is reached at 60–65% of design capacity. The findings indicate that the DME production process is technically feasible and economically attractive for industrial implementation, supporting Indonesia’s clean energy transition and reduction of LPG imports.